Emotional Intelligence, Spiritual Intelligence and Employee Performance: The Mediating Role of Communication Competence - Anita Rahmawaty; Wahibur Rokhman; Anton Bawono; Nafis Irkhami (International Journal of Business and Society, 2021)
The purpose of this study is to analyze the influence of emotional intelligence and spiritual intelligence on employee performance and the role of communication competence in mediating the influence of emotional intelligence and spiritual intelligence on employee performance. The samples are selected from employees (n = 196) of Islamic Microfinance Institutions in Pati, Central Java, Indonesia. The results of path analysis reveal that emotional intelligence and spiritual intelligence have a positive and significant influence on communication competence and employee performance, and communication competence partially mediates the influence of emotional intelligence and spiritual intelligence on employee performance. Therefore, it is recommended that Islamic Microfinance practitioners should improve employee performance through emotional intelligence, spiritual intelligence, and communication competence.